Evidence for Early Comprehension of Action Verbs. Issue 1 (2nd January 2019) - Nomikou, Iris; Rohlfing, Katharina J.; Cimiano, Philipp; Mandler, Jean M.
ABSTRACT: Applying an eye-tracking technique, we tested early verb understanding in 48 infants aged 9 and 10 months. Infants saw two objects presented side by side and heard a verb that referred to a common action with one of these objects (e.g., eating relating to a banana). The verbs were spoken by the parent in an interrogative manner in order to elicit a looking behavior in the infant. Results showed that 9-month-old infants did not show recognition of our test words. However, 10-month-old infants were able to understand a number of the tested verbs. In the discussion, we relate our findings to the nature of early verb representations.